Character as moral fiction - Alfano, Mark 1983- (Cambridge University Press, 2015)
"In Advertisers at Work, readers will gain insights from the most interesting people working in the field of advertising today, told in their own words. Guided by interviewer Dr. Tracy Tuten, 18 advertising leaders share their favorite stories, debunk the myths of advertising, make predictions on the industry's future, pay homage to the lions of the past, and offer insights into what it takes to win in the ad game today. Each chapter is devoted to one advertising executive, showcasing that person's unique vision and perspective into the world of advertising. Who are these leaders? Talent, perseverance, creativity, and pure grit set these people apart--and that's where their similarities end. With a mix of senior contributors and up-and-coming talent representing the creative crafts, media, planning, and account services from a variety of agencies and locales, this book pulls back the curtain and invites readers to live each leader's experiences up close. They'll learn from the advertisers at work. Every interview shows how advertising leaders have an impact on a day-to-day basis: charting strategy, making effective pitches, managing clients and key partners, calling in the creative muse, reading the public's mood, developing the right mix of media to launch a campaign, or pouncing on opportunities the rest of us can't see. This book: Shares the untold stories of senior executives and rising stars in advertising ; Demystifies the craft of advertising from the perspectives of creatives, media strategists, planners, and account executives ; Provides insights, strategies, and tactics readers can put to work immediately ; Offers predictions on the rapidly changing advertising landscape."--Publisher's website.